Pengaruh Penggunaan Media Mobile Learning Terhadap Hasil Belajar dan Kedisiplinan Peserta Didik Sekolah Dasar - Nani Rosanti; Mu’amar Mu’amar; Didik Tri Setiyoko (Peneliti.net, 2022)
In the 21st century, better education is needed in order to advance the quality and competitive young generation. Technology is one of the supporting elements of learning in the 21st century, so it can be used to improve.the quality of education. One.of them is using smartphones in learning. Mobile learning is one example. This study aims to.determine the effect of mobile learning media on social science learning.outcomes and the discipline of elementary school.students. The method used in this research is by experiment. The data. collection technique used saturated sampling. The total sample is 2 classes with each class consisting of 23 students. Class IV A as the experimental.class and class IV B as the control class. The experimental.class is a class using mobile learning media. The control. class is a class using conventional media, namely books. The subject matter used in the research is social science material about the cultural diversity of my people. After learning the students were given a test for learning outcomes.in the form of 10 multiple .choice questions and 20 items of disciplinary questions to the .experimental and control classes. This study .was analyzed using t test. The results obtained are aspects of learning outcomes, from the results of the t-test obtained a .significance (2-tailed) 0.000 <0.05 because 0.000 <0.05 H0 is rejected .and Ha is accepted which will be further described as below. So that the mobile learning media has an .influence on the learning outcomes of social science cognitive aspects of fourth grade students. The discipline aspect of the t test results obtained. a significance (2-tailed) .of 0.001 < 0.05 because 0.001 < 0.05 H0 was rejected .and Ha was accepted. So that the mobile learning media has an influence on the discipline of students. The conclusion .of this study is that the application of mobile learning media in social science learning about the cultural diversity of my nation has a positive influence on learning outcomes and discipline of fourth .grade students at SD Negeri Cipelem 01